ABOUT THE GLOBAL MAGNETIC FIELDS OF STARS - Bychkov, V. D.; Bychkova, L. V.; Madej, J. (Одеські астрономічні публікації, 2013)
We present are view of observations of the stellar longitudinal (eﬀective) magnetic ﬁeld (Be) and its properties. This paper also discusses contemporary views on the origin, evolution and structure of Be.